2023
DOI: 10.1515/cclm-2023-0055
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of humoral and cellular immunity after bivalent BNT162b2 vaccination and potential association with reactogenicity

Abstract: Objectives This study investigated the feasibility and clinical value of using a novel, automated and high-throughput SARS-CoV-2 Interferon Gamma Release Assay (IGRA), combined with total anti-SARS-CoV-2 antibodies assessment, for evaluating the immune response after bivalent BNT162b2 vaccination. Methods A cohort of healthcare workers, who already underwent primary vaccination and boosting with monovalent BNT162b2 vaccine, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Compared to Salvagno et al, the increase we observed was signi cant, although the p-value was close to 0.05 (i.e., p = 0.485). Our results agree with those of Salvagno et al on the fact that participants with lower cellular response at baseline were the ones who most bene t from a higher boost (3.3 and 2.9-fold increase after two weeks and one month in our studies, and 5.1-fold increase after one month according to Salvagno et al) (33).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Compared to Salvagno et al, the increase we observed was signi cant, although the p-value was close to 0.05 (i.e., p = 0.485). Our results agree with those of Salvagno et al on the fact that participants with lower cellular response at baseline were the ones who most bene t from a higher boost (3.3 and 2.9-fold increase after two weeks and one month in our studies, and 5.1-fold increase after one month according to Salvagno et al) (33).…”
Section: Discussionsupporting
confidence: 93%
“…The corresponding fold increase after the bivalent BA.4/5 booster was 1.4-1.7 and 1.9-2.6 (n = 18) and was therefore similar to that of the monovalent booster (34). In another study on 51 subjects, Salvagno et al identi ed a 1.8-fold increase in cellular response by means of an IFNγ release assay 1 month after the bivalent BA.4/5 booster, even if this increase was judged non-signi cant (33). The proportion of positive patients for IFNγ at baseline was 86.3% and increased at 98% 1 month afterwards.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Surrogate measures have hence been identified for mirroring the efficacy of the immune response, especially in individuals at higher likelihood of poor immunization (morbid, older, immunosuppressed), or in those at enhanced risk of risk of developing more severe more of illness [9] . The opportunity to assess both arms of the immune response by means of rapid, easy and relatively inexpensive laboratory tests (i.e., cellular immunity using interferon-γ release assay and humoral immunity with SARS-CoV-2 serology, respectively) [10] , is emerging as a valuable asset in both clinical practice and public health. To this end, early recognition of a blunted and or a faster decline of the immune response would enable to reliably identify individuals who may benefit most from additional or closer booster doses, as clearly shown by Achiron et al.…”
mentioning
confidence: 99%